Hari Jadi Kota Binjai Dalam Tinjauan Historis - Wiwik Lestari (Universitas Negeri Medan, 2017)
This study is a literature study that requires data, documents, and archives belonging to the government of Binjai. In addition, as a comparison, the researchers also used some of the literature related to the development of the city and also compares the birth city of Binjai with the birth of several other cities in Indonesia. Anniversary of the city of Binjai which has been celebrated annually on each May 17, is a form of worship to a symbol or emblem of history. The historical meaning taken from the heroic events Langkat Weigh War that occurred on May 17, 1872 Regional Binjai region that now. The basis for determining the anniversary of the city based on historical symbols is indeed feasible to use when we view it in terms of such viewpoints. But from the standpoint of the definition of the city, on the anniversary of Binjai that have been used have not been able to meet the eligibility criteria anniversary of the city. The value of heroism that are expected to stimulate a sense of nationalism unwitting townspeople have obscured the true facts, which is about how long Binjai actually reveal characteristic as a city. In this study, researchers reviewed the problem of determining the day Binjai. Binjai has now evolved into a city of services and industry need to re-pay attention the historiografi. Today Binjai not only should be commemorated and remembered every year, but it also must be determined in accordance with the facts and the actual data.